BiVO4 / MIL-68 (In) heterojunction composite material as well as preparation method and application thereof
Through the application of BiVO4/MIL-68(In) heterobonding composite materials in the photocatalytic-persulfate system, the problem of removing antibiotic pollution in water, especially ofloxacin, is solved, and efficient and stable degradation effect is achieved.
Patent Information
- Application Number
- CN202411661896.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The prior art is difficult to effectively remove antibiotic contamination in water, especially ofloxacin, and traditional methods are difficult to solve their residues in the water environment and risks to the public and animal health.
BiVO4/MIL-68(In) heterojunction composite material is used to enhance the degradation efficiency of the catalyst by photocatalytic-persulfate coupling through the electron transfer of the heterojunction material, and improve the degradation efficiency through the synergistic action of photocatalytic-persulfate.
The degradation efficiency of BiVO4/MIL-68(In) composite material is significantly improved, and ofloxacin in water can be degraded 100% under visible light conditions, and the photodegradation efficiency of more than 85% is maintained after four cycles, indicating that the material has good stability and recyclability.
Smart Images

Figure CN119633905A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic materials, the field of water treatment and the field of environmental management, and in particular to a photocatalytic-persulfate composite material for degrading antibiotics and application thereof. Background Art
[0002] Ofloxacin (OFL) belongs to the fluoroquinolone class of drugs and is widely used in the medical treatment of diseases. After ingestion by humans or livestock, most OFL cannot be completely absorbed in the body and is excreted through urination and other means, resulting in frequent detection in water environments. OFL remaining in the environment may induce large-scale bacterial resistance and antibiotic resistance, posing a serious risk to public and animal health. In addition, OFL has good chemical structure stability and is difficult to effectively remove by traditional water pollution treatment methods. It has become a top priority to urgently find an effective method to remove antibiotic contamination in water.
[0003] As one of the advanced oxidation processes, photocatalysis generates free radicals (such as OH· and O2 - ·, etc.) to effectively degrade organic pollutants. The disadvantages of photocatalysis are also obvious, manifested in insufficient visible light absorption, high recombination rate of photoexcited electron-hole pairs resulting in low quantum yield of reactive substances, and weak adsorption capacity of pollutants. Persulfate activation mainly activates persulfate to produce effective sulfate radicals (SO4 - ·) and effectively degrade pollutants in water. However, the activation process of metal ions usually requires an acidic reaction environment, and a large amount of metal sludge will be produced after the reaction, causing secondary pollution. Many studies have found that photocatalysis and persulfate activation have a positive synergistic effect on the removal of antibiotics. Persulfate can capture photogenerated electrons to generate sulfate radicals through self-activation, and at the same time, promote the separation of photogenerated electron-hole pairs, enhance the photocatalytic activity, and thus improve persulfate activation.
[0004] Bi-based and In-based semiconductor materials have always been widely concerned in the field of photocatalysis-persulfate. Due to the characteristics of simple composition, low toxicity, photocatalytic stability and excellent photocatalytic activity, they have great potential in removing antibiotics. The stable structure formed by the connection of metal oxide clusters and organic ligands in MOF materials can cause atomic structure changes and have certain catalytic properties. Among them, MIL-68 (In) has high temperature resistance, acid and alkali resistance, and strong physicochemical stability and has been widely studied. However, the actual application effect of MIL-68 (In) needs to be improved, and the catalytic degradation efficiency of the photocatalytic and persulfate combination process needs further study. In the present invention, MOF is used to successfully produce a composite material with a single material, and it is used for photocatalysis-persulfate to remove antibiotics, which can form a complementary and synergistic effect. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention provides a BiVO4 / MIL-68 (In) heterojunction composite material and its preparation method and application. The present invention can achieve the coupling of photocatalytic degradation and persulfate degradation, enhance the degradation efficiency of the catalyst through the electron transfer enhancement of the heterojunction material, and enhance the degradation efficiency by utilizing the synergistic effect of photocatalysis-persulfate degradation of pollutants.
[0006] The technical solution of the present invention is as follows:
[0007] A BiVO4 / MIL-68(In) heterojunction composite material, wherein the heterojunction composite material is a heterojunction structure formed by peanut-shaped granular BiVO4 embedded in hexagonal rod-shaped MIL-68(In);
[0008] The diameter of the peanut-shaped BiVO4 particles is 1-3 μm; the diameter of the hexagonal rod-shaped MIL-68 (In) is 5-10 μm.
[0009] The preparation method of the BiVO4 / MIL-68 (In) heterojunction composite material comprises the following steps:
[0010] (1) Preparation of MIL-68 (In):
[0011] Dissolve In(NO3)3·4H2O in DMF, stir well, add organic ligand 1,4-phthalic acid, continue to stir well, and transfer to a polytetrafluoroethylene liner; seal the polytetrafluoroethylene liner in a stainless steel autoclave and keep it at 100-120°C for 40-48 hours, wash and dry the obtained solid after cooling, and obtain MIL-68(In);
[0012] (2) Preparation of BiVO4 / MIL-68(In) heterojunction composite materials:
[0013] First, the vanadium source NH4VO3 is dissolved in deionized water and stirred to form solution A. Then, MIL-68(In) is dissolved in ethylene glycol and a bismuth source Bi(NO3)3·5H2O is added and stirred to form solution B. Then, solution A is slowly added to solution B to form a mixed solution. The solution is stirred evenly and transferred to a polytetrafluoroethylene-lined autoclave. The mixed solution is subjected to a hydrothermal reaction at a temperature of 100-150°C for 15-18h. After cooling, the solution is washed and dried to obtain the BiVO4 / MIL-68(In) heterojunction composite material.
[0014] Preferably, in step (1), the molar ratio of In(NO3)3·4H2O:1,4-phthalic acid is 1-1.2:1-1.5.
[0015] Preferably, in step (1), the mass volume ratio of In(NO3)3·4H2O to DMF is 23-26:1-1.2 mg / mL.
[0016] Preferably, in step (2), the mass ratio of NH4VO3, MIL-68(In), and Bi(NO3)3·5H2O is 3-4.5:1-1.5:12-15.
[0017] Preferably, in step (2), in solution A, the ratio of NH4VO3 to deionized water is 11-13:1-1.3 mg / mL; in solution B, the ratio of MIL-68(In) to ethylene glycol is 4-11:1-1.2 mg / mL.
[0018] The present invention also provides an application of the BiVO4 / MIL-68(In) heterojunction composite material, that is, the BiVO4 / MIL-68(In) heterojunction composite material is used to degrade antibiotics.
[0019] Preferably, the antibiotic is ofloxacin.
[0020] Preferably, the antibiotic is present in the mobile phase water.
[0021] Furthermore, the BiVO4 / MIL-68(In) heterojunction composite material activates persulfate to generate h in a photocatalytic-persulfate system under visible light conditions. + , O2 - and 1 O2 is the dominant free radical, and SO4 - · and ·OH secondary free radical active substances, thereby degrading antibiotics.
[0022] The beneficial technical effects of the present invention are:
[0023] 1. The present invention combines BiVO4 / MIL-68(In) for photocatalysis-persulfate degradation for the first time. BiVO4 and MIL-68(In) have excellent matching in potential energy and energy band gap, and the heterojunction material formed can effectively solve the problems of low visible light response, low electron conductivity and annihilation of photogenerated carriers.
[0024] 2. The morphological characteristics of BiVO4 / MIL-68(In) synthesized by the present invention using a stable organic ligand as a precursor are that MIL-68(In) is the main body and BiVO4 is embedded thereon. The overall particle size of BiVO4 is at the micron level, the core shape is peanut-shaped, and the overall peanut-shaped particles are clustered or exist alone; the overall particle size of MIL-68(In) is about 5-10μm, and the morphology is a hexagonal rod structure. BiVO4 is embedded in the gaps or surface of MIL-68(In), and the overall structure formed has a large specific surface area, which can enhance the adhesion of pollutants for effective degradation.
[0025] 3. The BiVO4 / MIL-68(In) material prepared by the present invention belongs to a Z-type heterojunction structure. Heterojunction type composite materials have higher potential energy, higher electronic conductivity and more effective electron-hole separation performance.
[0026] 4. The photocatalytic-persulfate process carried out by the present invention can significantly improve the degradation efficiency of the BiVO4 / MIL-68(In) composite material. The experimental results show that the degradation effect of the BiVO4 / MIL-68(In) composite catalyst at the same dose is significantly improved after adding persulfate during the photocatalytic process, which shows that the composite material of the present invention can couple the photocatalytic process and persulfate well, and also solves the defects of the composite material in the photocatalytic process and activated persulfate.
[0027] 5. Under visible light excitation, the heterojunction composite material prepared by the present invention has a strong electrostatic attraction between the holes on the valence band of BiVO4 in the single material and the electrons on the conduction band of MIL-68 (In) due to the lower band gap energy, and the photogenerated electrons in the conduction band and the photogenerated holes in the valence band are quickly annihilated. Compared with the single-component material, the heterojunction material in the BiVO4 / MIL-68 (In) composite material produces more active substances, which effectively improves the photocatalytic-persulfate degradation performance of the material for ofloxacin.
[0028] 6. The experimental results show that in the water of the mobile phase, the BiVO4 / MIL-68(In) composite material can achieve 100% degradation of ofloxacin in water after irradiation with visible light (300W xenon lamp) for 25 minutes. After four cycles, the photodegradation efficiency of tetracycline is still as high as more than 85%, indicating that the composite material has good stability and recyclability and can effectively degrade antibiotics in water.
[0029] 7. The present invention has a simple preparation method, wherein the synthesis process of BiVO4 uses deionized water as a solvent, which reduces the cost and improves the economic benefits compared to most BiVO4 synthesis processes that require dilute nitric acid or sodium hydroxide as a solvent. The synthesis process has low energy efficiency and stable operation, and has potential application prospects in the field of photocatalysis-persulfate, and has great potential in practical application and large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The SEM images of the materials obtained in Example 1, wherein (a) is BiVO4, (b) is MIL-68(In), (c) and (d) are BiVO4 / MIL-68(In);
[0031] Figure 2 XRD patterns of BiVO4, MIL-68(In) and BiVO4 / MIL-68(In) obtained in Example 1;
[0032] Figure 3 The transient photocurrent diagram of BiVO4 / MIL-68(In)(BVM-75) obtained in Example 1;
[0033] Figure 4 This is the EIS impedance diagram of BiVO4 / MIL-68(In)(BVM-75) obtained in Example 1;
[0034] Figure 5 The photocatalytic-persulfate degradation diagram of ofloxacin by BiVO4, MIL-68(In) and BiVO4 / MIL-68(In) in Test Example 1;
[0035] Figure 6 The photocatalytic persulfate removal rate diagram of BiVO4 / MIL-68(In) on ofloxacin solution with different precursor dosages in Test Example 2;
[0036] Figure 7 The photocatalytic persulfate removal rate of BiVO4 / MIL-68(In)(BVM-75) on ofloxacin solutions of different concentrations in Test Example 3;
[0037] Figure 8 The photocatalytic persulfate removal rate diagram of BiVO4 / MIL-68(In)(BVM-75) on ofloxacin solutions with different pH values in Test Example 4;
[0038] Fig. 9 This is the cycle number-degradation efficiency diagram corresponding to the cyclic degradation of ofloxacin solution by BiVO4 / MIL-68(In)(BVM-75) in Test Example 5. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Embodiment 1:
[0041] This embodiment provides a BiVO4 / MIL-68 (In) heterojunction composite material and a preparation method thereof, and the specific steps are as follows:
[0042] S1. Dissolve 2 mmol (601 mg) of In(NO3)3·4H2O in 25 mL of DMF, stir well, add 2.4 mmol (398.7 mg) of organic ligand 1,4-phthalic acid, continue to stir well, and transfer to a polytetrafluoroethylene liner; seal the polytetrafluoroethylene liner in a stainless steel autoclave and keep it at 120°C for 40 hours. After cooling, wash and dry the obtained solid to obtain MIL-68 (In);
[0043] S2. Weigh 234 mg NH4VO3 and dissolve it in 20 mL deionized water and stir for 20 min to form solution A;
[0044] S3. Weigh 25, 75, 125 and 225 mg of MIL-68(In) respectively, disperse them evenly in 20 mL of ethylene glycol, add 970 mg of Bi(NO3)3·5H2O and stir for 20 min to form solution B;
[0045] S4, solution A is slowly added to solution B to form a mixed solution, and the mixture is stirred at 900 rpm on a magnetic stirrer for 30 min, and then the mixed solution is transferred to a polytetrafluoroethylene-lined autoclave, and subjected to a hydrothermal reaction at 110° C. for 15 h. After the autoclave is naturally cooled, washed and dried, the BiVO4 / MIL-68(In) composite material can be obtained.
[0046] The successfully composited materials were named according to the loading amount, namely BVM-x (x = 25, 75, 125, 225), where x represents the amount of MIL-68 (In) added. Figure 1 As shown, from Figure 1 (a) It can be seen that BiVO4 is peanut-shaped particles with a lateral diameter of 1-3 μm and a length of 2-8 μm; Figure 1(b) It can be seen that MIL-68 (In) is a hexagonal rod with a diameter of 3-10 μm, preferably 5-10 μm, and a length greater than 5 μm, preferably 10-200 μm; Figure 1 (c) and (d) it can be observed that BiVO4 is clustered or individually embedded on the surface of MIL-68(In) to form a stable composite material.
[0047] The XRD pattern of the material prepared in this example is as follows: Figure 2 As shown in the figure, it can be seen that the composite material simultaneously shows characteristic diffraction peaks of Bi2O2CO3 and MIL-68(In), indicating that the two single materials have been successfully composited.
[0048] The composite materials were tested by transient photocurrent response and electrochemical impedance spectroscopy to explore the charge carrier separation behavior and interfacial charge transfer resistance in the composite materials. Figure 3 The transient photocurrent response diagram of the composite material is presented in the figure. It can be seen from the figure that under the light condition, the current peaks of different materials respond quickly and reach a steady state. Among them, the heterojunction composite material BVM-75 shows the highest current intensity, and the single Bi2O2CO3 and MIL-68 (In) current peaks are significantly reduced, and the composite material is better in terms of repeated stability of current.
[0049] Figure 4 The corresponding impedance curves of various materials are presented in the figure. The smaller the curve radius, the smaller the resistance of the corresponding material charge transfer, so that more electron holes can be generated. The curve radius of MIL-68 (In) is the largest, followed by Bi2O2CO3, while the curve radius of BVM-75 is the smallest, which is significantly lower than that of a single material. This proves that the photogenerated electrons of the heterojunction composite material have the smallest migration resistance and the largest charge separation efficiency.
[0050] Test Example 1:
[0051] The BiVO4 / MIL-68(In) composite material prepared in Example 1 was used to degrade ofloxacin in a photocatalytic reactor to evaluate its photocatalytic-persulfate ability under visible light. At the same time, a single BiVO4 with a diameter of 1-3 μm and a single rod-shaped MIL-68(In) with a length of 5-10 μm were used as comparisons. The specific method is as follows:
[0052] Visible light irradiation was provided using a 300W xenon lamp and a 420nm UV cutoff filter (>420nm). 20mg of the composite material was dispersed into a photocatalytic reactor containing 100mL ofloxacin solution (the concentration of ofloxacin was 5mg / L). The adsorption was stirred in the dark for 30min to allow the catalyst and the pollutant to reach adsorption equilibrium. During illumination, about 1.5mL of the suspension was taken at intervals (5min) and then filtered with a syringe filter membrane (0.22μm) to remove catalyst particles. The degradation rate of ofloxacin was determined using a high performance liquid chromatograph.
[0053] Figure 5 The graph is a photocatalytic-persulfate degradation effect curve of the composite material prepared in Example 1 of the present invention on ofloxacin under visible light. As can be seen from the figure, after 20 minutes of illumination, the photocatalytic-persulfate degradation rates of ofloxacin using BiVO4, MIL-68 (In) and BiVO4 / MIL-68 (In) alone are 86.17%, 31.25% and 100%, respectively. This shows that the heterojunction material effectively improves the photocatalytic-persulfate degradation of ofloxacin compared with the single-component material.
[0054] Test Example 2:
[0055] The photocatalytic degradation of ofloxacin by persulfate of BiVO4 / MIL-68(In) composites under visible light was evaluated at different precursor dosages. The specific method is:
[0056] A 300W xenon lamp and a 420nm UV cutoff filter (>420nm) were used to provide visible light irradiation. The prepared composite materials with different precursor loadings (25mg, 75mg, 125mg, 225mg) were added to 100mL ofloxacin solution (5mg / L). The adsorption was run for 30min in the dark to allow the composite material and the antibiotic to reach adsorption equilibrium. Persulfate was added during illumination, and about 1.5mL ofloxacin solution was taken at intervals (5min). The degradation rate of ofloxacin was determined by high performance liquid chromatography.
[0057] Figure 6 The photocatalytic-persulfate degradation effect curve of the BiVO4 / MIL-68(In) composite material prepared in Example 1 of the present invention on ofloxacin (5mg / L) under visible light is shown in the figure. As can be seen from the figure, as the MIL-68(In) dosage increases from 75mg to 225mg, the degradation rate of the composite material on ofloxacin decreases from 100% to 61.15%. This is because the increase in the precursor reduces the number of active sites for the reaction, and the excessive precursor produces a "covering effect" that prevents the excitation of certain active sites.
[0058] Test Example 3:
[0059] In the photocatalytic reaction device, the effects of different antibiotic concentrations on the photocatalytic degradation of ofloxacin were evaluated. The specific method is as follows:
[0060] A 300W xenon lamp and a 420nm UV cutoff filter (>420nm) were used to provide visible light irradiation. The prepared composite material (BVM-75) was added to 100mL ofloxacin solutions of different concentrations (5mg / L, 10mg / L, 20mg / L). The adsorption was run for 30min in the dark to allow the composite material and the antibiotic to reach adsorption equilibrium. During illumination, about 1.5mL of tetracycline solution was taken at intervals (5min). The degradation rate of ofloxacin was determined by high performance liquid chromatography.
[0061] Figure 7 The photocatalytic degradation effect of BiVO4 / MIL-68(In)(BVM-75) prepared in Example 1 of the present invention on different concentrations of ofloxacin solutions under visible light is shown in the figure. As can be seen from the figure, as the concentration of ofloxacin increases from 5mg / L to 20mg / L, the photodegradation rate decreases from 100% to 70.84%. This is because excessive ofloxacin molecules will compete for adsorption sites and reaction sites on the surface of the photocatalyst, resulting in a decrease in photocatalytic-persulfate efficiency. Therefore, the composite material prepared by the present invention has a good photocatalytic degradation effect when the concentration of ofloxacin is lower than 10mg / L.
[0062] Test Example 4:
[0063] In a photocatalytic reaction device, the effect of different pH values on the photocatalytic-persulfate degradation of ofloxacin was evaluated. The specific method is:
[0064] A 300W xenon lamp and a 420nm UV cutoff filter (>420nm) were used to provide visible light irradiation. The prepared composite material (BVM-75) was added to 100mL ofloxacin solution of different pH values (3, 5, 7, 9, 11). The adsorption was run for 30min in the dark to allow the composite material and the antibiotic to reach adsorption equilibrium. During illumination, about 1.5mL ofloxacin solution was taken at intervals (5min). The degradation rate of ofloxacin was determined by high performance liquid chromatography.
[0065] Figure 8The photocatalytic degradation effect of BiVO4 / MIL-68(In)(BVM-75) prepared in Example 1 of the present invention on ofloxacin solutions with different pH values under visible light - persulfate degradation curve. As can be seen from the figure, when the pH value increases from 5 to 11, the degradation rate remains above 99%, which indicates that the prepared composite material has a wide pH adaptability and has strong applicability in actual sewage treatment processes. When pH = 3, the adsorption and photodegradation efficiency decreases. The reason may be that the low initial pH value (pH = 3) and the excessive H + Can react with active species (O2 - ). Therefore, the composite material prepared by the present invention has a good photocatalytic-persulfate degradation effect when the pH is 5-11.
[0066] Test Example 5:
[0067] The long-term reusability and stability of the catalyst are key factors in practical water treatment processes. In the present invention, the BiVO4 / MIL-68(In)(BVM-75) composite material was used to carry out four cycles of photocatalytic degradation of ofloxacin-persulfate, where the concentration of ofloxacin was 5 mg / L. After each cycle, the composite material was taken out and simply rinsed with deionized water, filtered and dried before being put into the next cycle. The results are shown in Figure 2. Fig. 9 As shown in the figure, after 4 cycles, the photodegradation efficiency of ofloxacin was still above 85%, indicating that BVM-75 has good stability and recyclability. Fig. 9 The time on the middle horizontal axis includes the 30 minutes required to reach adsorption equilibrium under dark conditions.
[0068] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A BiVO4 / MIL-68(In) heterojunction composite material, characterized in that: The heterojunction composite material is a heterojunction structure formed by peanut-shaped granular BiVO4 embedded in hexagonal rod-shaped MIL-68 (In); The diameter of the peanut-shaped BiVO4 particles is 1-3 μm; the diameter of the hexagonal rod-shaped MIL-68 (In) is 5-10 μm.
2. The method for preparing the BiVO4 / MIL-68(In) heterojunction composite material according to claim 1, characterized in that: The steps include: (1) Preparation of MIL-68 (In): Dissolve In(NO3)3·4H2O in DMF, stir well, add organic ligand 1,4-phthalic acid, continue to stir well, and transfer to a polytetrafluoroethylene liner; seal the polytetrafluoroethylene liner in a stainless steel autoclave and keep it at 100-120°C for 40-48 hours, wash and dry the obtained solid after cooling, and obtain MIL-68(In); (2) Preparation of BiVO4 / MIL-68(In) heterojunction composite materials: First, the vanadium source NH4VO3 is dissolved in deionized water and stirred to form solution A. Then, MIL-68(In) is dissolved in ethylene glycol and a bismuth source Bi(NO3)3·5H2O is added and stirred to form solution B. Then, solution A is slowly added to solution B to form a mixed solution. The solution is stirred evenly and transferred to a polytetrafluoroethylene-lined autoclave. The mixed solution is subjected to a hydrothermal reaction at a temperature of 100-150°C for 15-18h. After cooling, the solution is washed and dried to obtain the BiVO4 / MIL-68(In) heterojunction composite material.
3. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of In(NO3)3·4H2O:1,4-phthalic acid is 1-1.2:1-1.
5.
4. The preparation method according to claim 2, characterized in that: In step (1), the mass volume ratio of In(NO3)3·4H2O to DMF is 23-26:1-1.2 mg / mL.
5. The preparation method according to claim 2, characterized in that: In step (2), the mass ratio of NH4VO3, MIL-68(In), and Bi(NO3)3·5H2O is 3-4.5:1-1.5:12-15.
6. The preparation method according to claim 2, characterized in that: In step (2), in solution A, the ratio of NH4VO3 to deionized water is 11-13:1-1.3 mg / mL; in solution B, the ratio of MIL-68(In) to ethylene glycol is 4-11:1-1.2 mg / mL.
7. Use of the BiVO4 / MIL-68(In) heterojunction composite material according to any one of claims 1 to 6, characterized in that: The BiVO4 / MIL-68 (In) heterojunction composite material is used for degrading antibiotics.
8. The use according to claim 7, characterized in that: The antibiotic is ofloxacin.
9. The use according to claim 7, characterized in that: The antibiotic is present in the mobile phase water.
10. The use according to claim 7, characterized in that: The BiVO4 / MIL-68(In) heterojunction composite material can activate persulfate to generate h in a photocatalytic-persulfate system under visible light conditions. + , ·O 2- and 1 O2 is the dominant free radical, and SO 4- · and ·OH secondary free radical active substances, thereby degrading antibiotics.
Citation Information
Patent Citations
Preparation method of hexagonal-tube-shaped indium oxide with complex as precursor
CN105668612A
Visible-light-responsive peanut-shaped bismuth vanadate and preparation method thereof
CN111790372A
PDI / MOF heterojunction photocatalyst and preparation method and use method thereof
CN112718009A
Preparation method and application of BiOCl / Fe-MOFs composite catalytic material
CN113058655A
Preparation method and application of ZnIn2S4 nanosheet coated BiVO4 microrod core-shell heterojunction catalyst
CN114653381A